Carbon dioxide adsorption and desorption study using bimetallic calcium oxide impregnated on iron (III) oxide - Lahuri, Azizul Hakim; Yarmo, Mohd Ambar; Marliza, Tengku Sharifah; Abu Tahari, Maratun Najiha; Samad, Wan Zurina; Dzakaria, Norliza; Yusop, Muhammad Rahimi (Scientific.Net, 2017)
Bimetal adsorbent system of calcium oxide impregnated on iron (III) oxide were evaluated as a potential source of basic sites for CO capture. The adsorbents were prepared by impregnation method were calcined at 200 until 600 °C. Several characterizations were carried out using XRD, BET and CO -TPD analysis. The CaO loading increased the basicity of the adsorbent signicantly enhance the CO chemisorption. Furthermore, it drastically reduced the desorption temperature to 310-490 °C, which is important in chemisorption aspect. The CaO/Fe O 200 which calcined at 200 °C was found to be most ecient. The CO chemisorption (81.29 mg CO /g adsorbent) was contributed most compared to physisorption (4.64 mg CO /g adsorbent)